Intranasal Midazolam Premedication for Anxiolysis in Children Prior to Nitrous Oxide Sedation - Choubey, Shikha (Achievements and Challenges of Medicine and Medical Science Vol. 12, 2025)
Background: Children and adolescents show diverse maturity, personality, temperament, and emotions, which lead to a variety in their vulnerability and coping ability in dental situations. Therefore, dentists need a plethora of techniques to manage children. Midazolam, a benzodiazepine has enjoyed a lot of attention in recent years as a good pediatric sedative agent. Aim: The aim of the study was to compare the administration of 0.1 mg/kg intranasal midazolam as premedication against a normal saline control in alleviating anxiety relating to and increasing acceptance of nasal hood by child patients receiving nitrous oxide sedation for dental treatment. Materials and Methods: After ethical clearance and informed consent, on the basis of odd and even numbers patients were allocated to group midazolam or group normal saline, respectively. Thirty children between the ages of 4–8 years requiring bilateral endodontic treatment with Frankl’s negative or definitely negative behavior were selected. The physical parameters were recorded at the beginning and after the dental procedure; the time required for the procedure was also recorded. The level of cooperation during acceptance of the nasal mask by the patient was evaluated using the four-point scale. The sensory perception levels (alertness) and overall behavior of the child were evaluated using the first and fourth categories of the Houpt Behavior Rating scale. Results: Participants in group N consumed more time than group M. A Higher percentage of children were seen in the time frame of 31 minutes and more in group N and group M timings were largely concentrated around the 30 minutes or less mark. Midazolam premedication was more effective in improving the acceptance of the nasal hood in children than without premedication (p=.002308). Conclusion: In the present study, the combination of midazolam and nitrous oxide proved to be an effective combination, resulting in good to excellent behavior in children who were Frankl’s behavior rating definitely negative and negative. The operator could carry out the procedure at all stipulated 60 appointments, the combination of the two agents proved to be 100% safe there were no adverse reactions reported in both the groups and the physiologic markers were within limits. Clinical Significance: For successful sedation premedication with nitrous oxide, midazolam is an excellent premedication drug.